Acceptability and Uptake of Repeat Home-based HIV Counselling and Testing in Rural South Africa. Preliminary Data of the ANRS 12249 TasP Trial - (:unkn) unknown (My University, 2013)
BackgroundThe ANRS 12249 Treatment as Prevention (TasP) trial is assessing whether HIV testing of all members of a community, followed by immediate ART initiation of all HIV-infected individuals, regardless of immunological or clinical staging, will prevent onward sexual transmission and reduce HIV incidence in the same population. The implementation of universal and repeat home-based HIV testing is not documented yet in a high HIV incidence and prevalence context.MethodsA cluster-randomised trial is implemented using a phased-approach in the Hlabisa sub-district (KwaZulu Natal, South Africa) where more than 20% of adults are living with HIV. The trial started in March 2012; ten clusters are implemented in the first phase to assess the feasibility and acceptability of the two consecutive interventions (test then treat). The HIV testing strategy consists in a large range of community and clinic HIV testing options including the implementation of 6-monthly rounds of home-based HIV counselling and testing by dedicated counsellors. At each home visit, trial participants are administered individual questionnaires and offered a rapid HIV test.ResultsAs of April 30, 2013, 6 907 eligible subjects (16 years or above) were registered in six clusters and 5 122 (74%) were contacted. HIV status of 3 923 (76.5% of those contacted) was ascertained, 3 256 accepting the rapid HIV test at home and 667 being already aware of their HIV-positive status. We will present updated data from the first four trial clusters, where all eligible members of the community will have been offered three rounds of home-based HIV testing within 18 months. Uptake of HIV testing at each round will be reported. Uptake of repeat HIV testing will be measured among those testing HIV-negative at first round and who accept repeat HIV testing at rounds 2 and 3. We will also describe the reasons for HIV test refusal. Finally, we will present participants’ attitudes regarding repeat HIV testing, an
Keywords: African Research